PEMBUATAN SISTEM INFORMASI LAPORAN KEUANGAN ETAP BERBASIS WEB PADA UKM DI KOTA BATAM - Puspita Rama Nopiana; Evan Rosiska (LPPM Universitas Putera Batam, 2019)
Research has a problem that explains that: (1) the pioneered effort is not lasting and difficult to develop (2) the low level of education and knowledge in the field of accounting (3) the lack of understanding of information technology. The purpose of this study to make information systems ETAP web-based financial statements. The financial statements presented can make the financial statements of service companies, trade and industry. The method of experimental research, by making financial report software that can be utilized for business actors in companies engaged in services, trade and industry. The result of the research explains that ETAP financial statement information system created gives output following accounting process from the initial balance, general journal, and special, general ledger, and subsidiary ledger, trial balance, journal adjustment that are processing in a computerized manner so as to provide output in the form of financial statements consisting (income statement, statement of owner equity, balance sheet) making SIKBAP Accounting can petrify business actors in presenting financial statements in accordance with the standards.